Decomposition of Additive LMIs with Applications in Distributed Analysis of Interconnected LTI Systems. Issue 30 (2022) - Jokić, Andrej; Nakić, Ivica
Abstract: In this paper we present a simple technique which can be systematically used to obtain non-conservative decomposition for a class of linear matrix inequalities (LMIs) with an additive structure. By non-conservative decomposition we mean a suitable replacement of an additive LMI with a set of equivalent inequalities which are coupled by common variables. The results are applied on several stability/dissipativity analysis problems to produce analysis LMIs suitable for distributed computation.